EAHP 2010 survey on hospital pharmacy in Europe: Part 2 Procurement and distribution. Issue 5 (31st October 2012) - Frontini, Roberto; Miharija-Gala, Tajda; Sykora, Juraj
Abstract : Hospital pharmacies in Europe are responsible for supplying medicines and 56.2% of them also have responsibility for medical devices. The number of medicines listed in formularies varies from 246 to 1982, with the median being 960. Hospital pharmacies in western Europe usually procure their supplies direct from industry, while in eastern Europe medicines are mainly sourced from wholesalers. Own production is significant only in Denmark. Overall, 45.7% of pharmacies join in an alliance with another pharmacy to purchase their supplies. Distribution is mostly centralised (70.1%) and unit-dose supply is common in a few countries (European average 23.4%). Services are also provided to outpatients by 66% of pharmacies. Robotic dispensing is being implemented in few western European countries (mainly The Netherlands, Portugal and Spain), where in average 3.3% of hospitals used such systems in 2005 increasing to 6.7% in 2010. Approximately one third of hospitals use barcode technology for stock control and manual selection of items. Large hospitals have more automation than small hospitals.